Efficient fast Fourier transform-based solvers for computing the thermomechanical behavior of applied materials - Wicht, Daniel (Schriftenreihe Kontinuumsmechanik im Maschinenbau, 2022)
The mechanical behavior of many applied materials arises from their microstructure. Thus, to aid the design, development and industrialization of new materials, robust computational homogenization methods are indispensable. The present thesis is devoted to investigating and developing FFT-based micromechanics solvers for efficiently computing the (thermo)mechanical response of nonlinear composite materials with complex microstructures.